Prognostic significance of acquired copy‐neutral loss of heterozygosity in acute myeloid leukemia. Issue 17 (29th May 2015) - Gronseth, Christine M.; McElhone, Scott E.; Storer, Barry E.; Kroeger, Kathleen A.; Sandhu, Vicky; Fero, Matthew L.; Appelbaum, Frederick R.; Estey, Elihu H.; Fang, Min
<x xml:space="preserve">Abstract</x> BACKGROUND Chromosomal abnormalities are important in the diagnosis and prognosis of patients with acute myeloid leukemia (AML). Genomic microarray techniques detect recurrent copy‐neutral loss of heterozygosity (cnLOH) in addition to copy number aberrations. However, the clinical utility has not been fully established. Therefore, in the current study, the authors examined the prognostic impact of acquired cnLOH in patients with AML, including complete remission (CR) rate, duration of CR, and overall survival (OS). METHODS A total of 112 consecutive patients with AML who were undergoing chromosome genomic array testing (CGAT) at the Seattle Cancer Care Alliance were included in the current study. DNA from the bone marrow or blood was analyzed with a microarray platform with both single‐nucleotide polymorphism (SNP) probes and non‐SNP probes to identify acquired cnLOH. Results were correlated with cytogenetic, molecular, immunophenotypic, and other clinicopathological findings. RESULTS Patients with cnLOH demonstrated a shorter duration of CR (hazard ratio, 1.87; P =.04) and worse OS (HR, 1.82; P = .03). Multivariate analyses confirmed the independent predictive value of cnLOH for early disease recurrence (P =.02). These results largely reflected those in patients with intermediate and unfavorable cytogenetics. Most strikingly, 13q cnLOH was found to demonstrate a 6.64‐fold higher rate of disease recurrence (P =.006) and 3.45‐fold worse OS (P = .02) and was enriched with the FLT3‐ITD (Fms‐related tyrosine kinase 3‐internal tandem duplication) mutation. CONCLUSIONS CnLOH has important prognostic significance in patients with AML. CGAT can replace imbalance fluorescence in situ hybridization and the authors recommend the routine use of CGAT to detect cnLOH, particularly among patients with intermediate‐risk cytogenetics. Cancer 2015;121:2900–2908. © 2015 American Cancer Society.